THE IMPLEMENTATION OF GIST STRATEGY TO COMPREHEND ANALYTICAL EXPOSITION TEXT FOR ELEVENTH GRADERS OF SMA WACHID HASYIM 2 TAMA (RETAIN, 2013)
This study was descriptive qualitative which described how the eleventh graders of SMA Wachid Hasyim 2 Taman implemented GIST (Generating Interaction between Schemata and Text) strategy to comprehend analytical exposition text and the students’ comprehension on analytical exposition text after the implementation of GIST strategy. This study was carried out on first semester of XI language class in SMA Wachid Hasyim 2 Taman. The data taken from class observation during three days and interview with the English teacher showed that the students could implement GIST strategy but they still needed another strategy, which was translation. Besides that, GIST strategy had good effect in teaching learning process. It could bring interest; motivate the students to learn on reading activity. In terms of reading comprehension on analytical exposition after the implementation the strategy, students’ reading task showed good progress from the first task to the second one. Keywords:GIST, Analytical Exposition Text, Reading Comprehension, Eleventh Graders